Claudio Magris, Croce del Sud. Tre vite vere e improbabili (Altre Modernità, 2021)
Claudio Magris, Croce del Sud. Tre vite vere e improbabili(Milano, Mondadori, 2020, 132 pp. ISBN 978-88-0472-899-3)di Federico Prina